Immunogenicity, Effectiveness, and Safety of COVID-19 Vaccines in Rheumatic Patients: An Updated Systematic Review and Meta-Analysis - Kuo-Tung Tang; Bo-Chueh Hsu; Der-Yuan Chen (Biomedicines, 2022)
Background: Vaccination is one of the most important measures worldwide to halt the spread of the corona virus disease 2019 (COVID-19). However, the efficacy and safety of these vaccines in rheumatic patients are not well explored. Therefore, we conducted a systematic review and meta-analysis. Methods: We performed a literature search of the PubMed and EMBASE databases on 17 November 2021. Forty-seven studies relevant to the immunogenicity, efficacy/effectiveness, and safety of COVID-19 vaccines were selected. Results: Our results demonstrated that COVID-19 vaccination is effective in protecting rheumatic patients from severe illness caused by the virus. Both the humoral and cellular immunogenicity of vaccines were impaired in rheumatic patients, which were greatly enhanced after the second vaccine dose. Receiving anti-CD20 therapy was associated with impaired humoral immunogenicity. Adverse events due to COVID-19 vaccines in rheumatic patients were similar to those in healthy controls, except for an increased incidence of arthralgia. The incidence of disease flares after COVID-19 vaccination was low. Conclusion: Our systematic review indicated the importance of full vaccination in rheumatic patients. Withholding anti-CD20 therapy was found to be potentially beneficial for the immunogenicity. Furthermore, the vaccines were found to be safe in general. Despite significant heterogeneity between studies, we recommend that rheumatic patients receive these vaccines amidst the global pandemic.